FORMULASI VANISHING CREAM MINYAK ATSIRI SERE (Cymbopogon citratus (DC) Stapf) DAN UJI SIFAT FISIKNYA SERTA UJI AKTIVITAS REPELAN TERHADAP NYAMUK Aedes aegypti BETINA - Ikhsanudin, Azis (Pharmaciana, 2011)
Essential oil of sere leaf has been proven as repellant against mosquitoes. Thisresearch aims to know about the influence of concentration sere essential oil(Cymbopogon citratus (DC) Stapf) in a vanishing cream bases to physical propertiesand repellant testing against female Aedes aegypti mosquitoes. Essential oil of sere(Cymbopogon citratus (DC) Stapf) was isolated with steam water distillation and wasevaluated the organoleptic appearance and refraction index. Furthermore, theessential oils were formulated in a vanishing cream base with the different formulas,contain formula I: 20% v/w; formula II: 30% v/ w and formula III: 40% v / w. Then thisthree formulas were evaluated for physical properties including adhesive, dispersiveand the repellent activity testing against female Aedes aegypti mosquitoes amount oftwenty mosquitoes per cage while seven female volunteers as the probandus. The datahave been analyzed using Kolmogorov-Smirnov test and t-test (Main-Whitney), with95% signifancy level. The results were obtained that the adhesion of formula I: 0.90 ±0.029 seconds, formula II: 0.60 ± 0.017 seconds, formula III: 0.46 ± 0.040 seconds,while the dispersion of formula I is 64.89 ± 4.559 cm2, the formula II is 64.71 ± 4.600 cm2 and the formula III is 54.96 ± 14.783 cm 2. The longest time repellent was formula IIIshowed 3014.2 ± 20.163 seconds or 50.23 minutes. It was concluded that the increase ofconcentration essential oils of sere leaf followed by the increase of repellant activity.